2019
DOI: 10.2490/prm.20190019
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prevertebral Soft Tissue Thickening and Dysphagia in Cases of Traumatic Cervical Spinal Cord Injury

Abstract: The objectives of this study were to clarify whether prevertebral soft tissue (PVST) thickening increases the risk of dysphagia, to identify at which vertebral level determining PVST thickness is useful, and to determine cutoff values. Methods: A total of 80 patients with traumatic cervical spinal cord injury (TCSCI) treated over a 43-month period at a single regional institution specializing in cervical spinal cord injuries participated in the study. The exclusion criteria were having undergone anterior cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Prevertebral soft tissue thickness (PVST) was measured using midsagittal sections on cervical CT (GE Healthcare, Waukesha, WI, USA) at C2, C3, and C6, as previously described. [ 9 ] The prevalence of high-intensity in the prevertebral space was evaluated using STIR midsagittal MR images (Exelart 1.5 T MRI System; Toshiba Co., Ltd., Tokyo, Japan). We assessed the prevertebral high-intensity area (HIA) and high-intensity anteroposterior width (HIW) at each vertebral level from C1 to C7 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prevertebral soft tissue thickness (PVST) was measured using midsagittal sections on cervical CT (GE Healthcare, Waukesha, WI, USA) at C2, C3, and C6, as previously described. [ 9 ] The prevalence of high-intensity in the prevertebral space was evaluated using STIR midsagittal MR images (Exelart 1.5 T MRI System; Toshiba Co., Ltd., Tokyo, Japan). We assessed the prevertebral high-intensity area (HIA) and high-intensity anteroposterior width (HIW) at each vertebral level from C1 to C7 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This has been pointed out by Mitsuishi et al in their discussion on the difficulty of setting the upper limit for PVST anterior to C4 and C5 owing to the characteristics of the soft tissue. [9] Magnetic resonance imaging (MRI) is useful for diagnosing and assessing discoligamentous cervical spine injuries in patients without skeletal injuries. In particular, prevertebral hyperintensity on T2-weighted MRI, which reflects prevertebral edema, fluid collection, or hemorrhage, is associated with initial cervical segmental instability in patients with CSCI without major bone injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that the presence of a tracheostomy is a significant independent risk factor for dysphagia after cSCI [14,31,[72][73][74]. One study reported a threefold risk (RR: 3.67) of dysphagia with a tracheostomy following cSCI [73].…”
Section: Dysphagia Due To Medical Managementmentioning
confidence: 99%